Cultivating Pancasila Values: Analyzing the Ideology of Diversity in Presidential Speeches and Its Impact on Elementary Education in Indonesia - Suryo Hanjono; Farida Nugrahani; Benedictus Sudiyana (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study examines the ideology of diversity as reflected in the Independence Day speeches of the President of the Republic of Indonesia in 2022 and 2023 and its implications for basic education. The research explores how linguistic elements in these speeches convey ideological messages that align with Pancasila values.A qualitative descriptive approach with literature review methods was employed. Data were collected by analyzing linguistic and ideological elements in the speeches, using Teun A. van Dijk’s critical discourse analysis model. Macrostructure, superstructure, and microstructure levels were explored to uncover ideological meanings. Triangulation was applied to validate the findings.The findings reveal that the speeches reflect an ideology of diversity through themes emphasizing faith, morality, cultural respect, mutual cooperation, independence, and critical thinking. These themes align with Pancasila principles and address national priorities such as managing diversity, fostering collaboration during the pandemic, and enhancing resource optimization.The speeches underscore the role of the government in promoting national unity and progress. In the context of basic education, the ideology of diversity can be integrated into learning through Indonesia’s independent curriculum. Primary school teachers can incorporate these values into teaching materials, school culture, the Pancasila student profile project, and other related activities.This study highlights the potential of presidential speeches to influence educational practices and policies. It provides a foundation for developing teacher training programs that foster students’ personalities as future contributors to national unity and diversity.